IMPLEMENTASI BIMBINGAN KELOMPOK PRA NIKAH BAGI SISWA SMA NEGERI 1 BAKAM KABUPATEN BANGKA - Sholeh Marsudi, Muhammad; Zakirman, Al Fakhri; Musdalifah, Musdalifah (Berajah Journal, 2024)
This article aims to explore the premarital guidance process for students of SMA Negeri 1 Bakam, Bangka Regency. This research is field research with a qualitative descriptive approach. Research subjects included students of SMA Negeri 1 Bakam, Bangka Regency. Data was obtained through the PAR (Participatory Action Research) method, namely research that involves all parties in active research together in one concrete action. The research results show that there is still a lack of awareness of the importance of pre-marital guidance and there are still many students who do not understand the impact of early marriage. The main obstacles include a lack of cooperation with related parties such as the Ministry of Religion, academics and related agencies to provide pre-marital guidance. Factors that influence this problem include a lack of awareness of the importance of pre-marital guidance for students, there are still many students who do not understand the impact of early marriage and thorough marriage preparation in building a household and there is still a lack of role of guidance counselors in providing pre-marital guidance for students. at school. This article provides an in-depth view of the need for the pre-marital guidance process for students and students, especially in high schools.